Autoritatea bancară europeană - Gribincea, Lilia (My University, 2013)
The European Banking Authority was established by the Regulation (EC) No. 1093/2010 of the European Parliament and of the Council on 24 November 2010. The Authority shall have inter alia the following tasks: (a) to contribute to the establishment of high-quality common regulatory and supervisory standards and practices, in particular by providing opinions to the European Union institutions and by developing guidelines, recommendations, and draft regulatory and implementing technical standards; b) to stimulate and facilitate the delegation of tasks and responsibilities among competent authorities; c) to cooperate closely with the European Systemic Risk Board (ESRB), in particular by providing the ESRB with the necessary information for the achievement of its tasks and by ensuring a proper follow up to the warnings and recommendations of the ESRB; d) to organise and conduct peer review analyses of competent authorities, including issuing guidelines and recommendations and identifying best practices, in order to strengthen consistency in supervisory outcomes; e) to undertake economic analyses of markets to inform the discharge of the Authority’s functions; f) to foster depositor and investor protection; g) to contribute to the consistent and coherent functioning of colleges of supervisors, the monitoring, assessment and measurement of systemic risk, the development and coordination of recovery and resolution plans, providing a high level of protection to depositors and investors throughout the European Union and developing methods for the resolution of failing financial institutions and an assessment of the need for appropriate financing instruments etc.